World Accumulation and Planetary Life, or, Why Capitalism Will Not Survive until the ‘Last Tree is Cut - Moore, Jason W. (Masyarakat: Jurnal Sosiologi, 2019)
How does capitalism work through the web of life? How can we begin to understand capitalism not simply as an economic system of markets and production and a social system of class and culture, but as a way of organising nature? This essay explores a relational, historical, and geographical answer to these questions. Arguing that capitalism is a world-ecology that joins the accumulation of capital, the pursuit of power, and the co-production of webs of life in dialectical unity, Moore offers a way to understand today’s planetary crisis. That crisis marks a turning point not only in the planet’s climate system, but in ways of organization power, production, and reproduction over the past five centuries. Planetary justice in the twenty-first century will need to make sense of catastrophic climate change not just as matter of too many greenhouse gases, but also as a moment of the climate class divide, climate patriarchy, and climate apartheid.